PSEUDOTANIAN COINS OF SOGD - Musakayeva A. A (Galaxy International Interdisciplinary Research Journal, 2021)
The article deals with the problems of the pseudotanian coinage of Sogd. The classification of coins developed by the author is presented. The issues of dating these coins are considered.